Analysis of Strain and Intermixing in a Single Layer Ge/Si dots using polarized Raman Spectroscopy - PEROVA, TANIA; MOORE, ROBERT (My University, 2006)
The built-in strain and composition of as-grown and Si-capped single layers of Ge?Si dots grown at various temperatures (460?800 ?C) are studied by a comparative analysis of the Ge-Ge and Si-Ge modes in the polarized Raman spectra of the dots. A pronounced reduction of the strain and Ge content in the dots after deposition of the cap layer at low temperatures is observed, indicating that strain-induced Si diffusion from the cap layer is occurring. For large dots grown at 700?800 ?C the observations are in agreement with a model of the Ge?Si dot consisting of a Si-rich boundary region and a Ge-rich core.
PUBLISHED
Keywords: Mechanical and Manufacturing Engineering